Inclusive public spaces for water management in rural India - Wong, Tsz Wai (Kansas State University, 2018)
In underprivileged communities in developing countries, water is essential for basic survival. Particularly for rural communities, water supports irrigation for agriculture and, hence, the livelihood of villagers. Based on a forecast by the Asian Development Bank, India is expected to reach a water deficit of 50% by 2030 (Dutta, 2017). Without awareness of conservation and efforts to conserve water resources and protect them from being polluted by industries and communities, rural Indian communities will continue to suffer from water mismanagement and the loss of potential long-term environmental, social, and economic benefits that water can bring to a community. Nonetheless, better water management is attainable in rural communities. Given the model Indian villages that have been transformed into sustainable communities by implementing and managing effective blue-green infrastructure through community participation, landscape architects are proven that they are capable of various roles in leading, initiating, and providing design and technical support for water infrastructure projects of different scales in rural India. Since stewardship and maintenance of these systems are critical for long-term effectiveness, the core idea of this design project is leveraging local efforts and community power to build and maintain functional water infrastructure as a better, more sustainable water management strategy. In this study, public space associated with water infrastructure is considered as a potential driver for local efforts to maintain the water management landscape when those public spaces are designed for inclusiveness and diversity. Thus, the project goal is to create or transform the public space associated with existing water infrastructure into an inclusive, productive community place that can generate environmental, social, and economic benefits, as a strategy for sustainable water management in rural India. Currently, the proposed water management landscape in this study is a diverse public space shared by community members of different ages, genders, classes, castes, and religions. The research methodology divides into three phases. The first phase addresses the general water issues and the cultural background of rural India through literature and preliminary site inventory using the GIS data provided by the Panchayat of Dhamori. The second phase presents the perceptions of villagers in Dhamori about using water and public space after collecting quantitative and qualitative data through site observation and participatory planning. By synthesizing and analyzing the knowledge generated from the participatory process on-site, the final phase interprets and addresses the emergent problems through developing a design framework for conceptual site design.
A design framework of the public spaces associated with water infrastructure in rural India to promote sustainable water management
Keywords: Sustainable water management; Public space; Rural; India; Participatory planning; Landscape architecture